Pengaruh Budaya Organisasi dan Remunerasi Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Personil di Kepolisian Resort (POLRES) Metro Jakarta Selatan - Yudho Negoro; Imam Muhtadin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of organizational culture and remuneration on job satisfaction and its impact on personnel performance at the South Jakarta Metro Resort Police. A quantitative approach is used with descriptive and associative research types. The research results show that organizational culture has a positive and significant effect on job satisfaction (coefficient 0.489; p<0.05) and personnel performance (coefficient 0.793; p<0.05). Remuneration also has a positive effect on job satisfaction (coefficient 0.353; p<0.05) but not significantly on personnel performance (coefficient -0.053; p>0.05). Job satisfaction has a significant influence on personnel performance (coefficient 0.135; p<0.05). However, neither organizational culture nor remuneration has a significant effect on personnel performance through the mediation of job satisfaction. This research underlines the importance of a conducive organizational culture and fair remuneration in increasing job satisfaction and personnel performance. These findings are relevant for the development of human resource management strategies in police institutions.